A randomized clinical trial comparing the use of a pancreatic duct stent or a pancreatic duct guidewire to facilitate bile duct cannulation - Azar, Riad (2010)
Among cases of difficult biliary cannulation, alternatives to precut sphincterotomy include use of a pancreatic duct (PD) stent (PDS) or guidewire (PDW) to facilitate common bile duct cannulation (CBDC). We present the preliminary results from an ongoing, multicenter, randomized trial.